2019
DOI: 10.1177/1934578x19850992
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Needle, Cone, and Branch Oils From Vietnamese Pinus cernua

Abstract: Conifers are well represented in Vietnam where a new pine species has been recently discovered in Son La province: Pinus cernua, synonym P. armandii ssp. xuannhaensis. The compositions of needle, cone, and branch oils have been investigated by gas chromatography (retention index), gas chromatography-mass spectrometry, and 13 C nuclear magnetic resonance. Myrcene (47.0%) was the main component of needle oil, followed by β-pinene (28.4%) and α-pinene (12.5%). Branch oil also contained myrcene (32.8%), α-pinene (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…These were α-pinene-oxide (17), α-phellandren-8-ol (23), δ–elemene (38), cyclosative (43), ylangene (44), and butylated hydroxytoluene (57). These compounds were described for the genus Pinus ( Zhang and Wang, 2010 ; Nikolić et al., 2018 ; Thai et al., 2019 ; Ji and Ji, 2021 ; Mohamed et al., 2022 ), but none for the oleoresin. Those already described for L. decidua were mainly found in the bark, needle and wood samples only.…”
Section: Resultsmentioning
confidence: 99%
“…These were α-pinene-oxide (17), α-phellandren-8-ol (23), δ–elemene (38), cyclosative (43), ylangene (44), and butylated hydroxytoluene (57). These compounds were described for the genus Pinus ( Zhang and Wang, 2010 ; Nikolić et al., 2018 ; Thai et al., 2019 ; Ji and Ji, 2021 ; Mohamed et al., 2022 ), but none for the oleoresin. Those already described for L. decidua were mainly found in the bark, needle and wood samples only.…”
Section: Resultsmentioning
confidence: 99%
“…xuannhaensis L. K. Phan) was published by Averyanov et al ( 2017), we realized we had not identified this species correctly and the correct name of this species was P. cernua. The oil composition of different parts of P. cernua was identified by GC, GC/MS and NMR as follows: from the needles including α-pinene (12.5%), β-pinene (28.4%), myrcene (47%) and limonene (4.6%); from the cones including α-pinene (44.1%), β-pinene (8.1%), myrcene (11.5%) and E-β-caryophyllene (6.1%); from the twigs including α-pinene (17.9%), β-pinene (9.8%), myrcene (32.8%), limonene (22%), -cadinene (3.1%) and E-β-caryophyllene (2.3%) (Tran et al, 2019).…”
Section: Introductionmentioning
confidence: 99%